2015
DOI: 10.1039/c5ra19201c
|View full text |Cite
|
Sign up to set email alerts
|

High quantum-yield luminescent MoS2 quantum dots with variable light emission created via direct ultrasonic exfoliation of MoS2 nanosheets

Abstract: MoS2 QDs with high quantum-yield, variable photoluminescence emission properties and good biocompatibility are studied and applied to the bio-imaging field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 32 publications
8
52
0
Order By: Relevance
“…We found QY ≈ 2.54% under pH ≈7, which is improved up to ≈2.78% for under basic conditions (pH ≈ 13). However, there are literatures which have shown that it could be increased up to ≈4.84% under sonication with ion intercalation method for alkaline medium …”
Section: Resultsmentioning
confidence: 99%
“…We found QY ≈ 2.54% under pH ≈7, which is improved up to ≈2.78% for under basic conditions (pH ≈ 13). However, there are literatures which have shown that it could be increased up to ≈4.84% under sonication with ion intercalation method for alkaline medium …”
Section: Resultsmentioning
confidence: 99%
“…The QY of MoS 2 quantum dots is reported from 2.6% to 4.84% (Wu et al, 2015;Wang and Ni, 2014) and the QY of WS 2 quantum dots is reported from 1.8% to 4% Yan et al, 2016). The MoS 2 and WS 2 quantum dots also shows excitation-dependent emission.…”
Section: Comparison Of Graphene and Graphene-like 2d Materails As Donorsmentioning
confidence: 88%
“…The MoS 2 and WS 2 quantum dots also shows excitation-dependent emission. The fluorescence emission spectra of MoS 2 QDs can be modulated from blue, green to red (Wu et al, 2015) and the fluorescence of WS 2 quantum dots was mainly at the blue to green light region under various excitation wavelength .…”
Section: Comparison Of Graphene and Graphene-like 2d Materails As Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain TMD QDs, the X‐M‐X bond in the plane needs to be broken and then generate edge atoms. Because of the weak van der Waals force between TMD layers, TMD QDs can be easily obtained by ultrasonic grinding or solvent heat treatment (Gan et al, ; Gao, Wang, Ran, & Li, ; Gopalakrishnan et al, ; Gopalakrishnan, Damien, & Shaijumon, ; Ha, Han, Choi, Park, & Seo, ; Li et al, ; Lin et al, ; Lin et al, ; Qiao et al, ; Ren et al, ; Štengl, Tolasz, & Popelková, ; Wu, Zhang, Ma, Qiu, & Zhang, ; Xu, Li, & Wu, ; Yong et al, ; Yuwen et al, ). Zhang et al () prepared many TMD QDs (MoS 2 , WS 2 , ReS 2 , TaS 2 , MoSe 2 , and WSe 2 ) from the corresponding bulk TMD crystals at room temperature by combining the grinding and ultrasonic processes.…”
Section: Classification Of Quantum Dotsmentioning
confidence: 99%